From waste to functional material: POME-derived Ag/g-C3N4 for pharmaceutical degradation and energy storage - Allysha Riziana, Reduan; Reshma, Nair; Danielson Ngo, Joseph; Bhaven, Patel; Micky A, Vincent; Priyanka, Ganguly; Devagi, Kanakaraju (Elsevier, 2026)
Antibiotic pollution in aquatic ecosystems and the growing demand for sustainable energy storage highlight the need for multifunctional materials with adjustable interfacial properties. This study developed silver (Ag)-modified g-C3N4 composites through a green method using palm oil mill effluent (POME) extract as a natural reducing agent. Structural and optical characterizations (FTIR, SEM-EDX, XRD, UV–Vis DRS, BET surface area) confirmed the incorporation of Ag nanoparticles, thereby reducing the bandgap from 2.80 to 2.30 eV and improving visible-light absorption. The 10% Ag/g-C3N4 photocatalyst showed efficient charge separation and interfacial electron transfer, achieving a maximum oxytetracycline (OTR) removal of 74.8% under simulated solar light. Process optimization using response surface methodology (Box–Behnken design) identified catalyst dose and solution pH as key factors, with optimal conditions (0.06 g catalyst, 14 ppm OTR, pH 12) producing performance in line with model predictions. Electrochemical tests further indicated that Ag addition enhanced the charge-storage capacity of g-C3N4, with the 8% Ag/g-C3N4 composite displaying the highest specific capacitance (43.59 mF g−1 at 2 mA) and energy density (6.05 μWh kg−1), along with the lowest charge-transfer resistance. This improvement is due to better electrical conductivity and ion transport at the Ag/g-C3N4 interface. In a textile-based supercapacitor, the 8% Ag composite with 1 M Na2SO4 hydrogel delivered superior performance (2.96 mF g−1, 0.411 μWh kg−1, and 128 μWh kg−1), showing enhanced redox activity and ion mobility. These results demonstrate that interfacial engineering of Ag/g-C3N4 is a promising approach for creating dual-functional materials for energy storage and environmental clean-up.